Aspek Pemidanaan Dalam Hukum Perkawinan - Khaeron Sirin (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2010)
The article attemptsto critisize the idea of punishment against unregistired marriage-such as surreptious marriage, temporary contact marriage, and polygamy without legal permission from the court-which has emerged since early 2010 and has caused polemic among the society. Many people support this idea, while other people reject it. those who support the idea see that the punishment against unregistered marriage would restrict the abusive marriage, protect the rights of women and children, and bring about cultre of law and order among the society in terms of marriage. on the countary, those who reject the idea argue that unregistered marriage is considered religously legal and valid -especially in islam when it is conducted in accordance with the rewuirement and the principles of marriage.